Implementing Semantic Mapping to Improve Vocabulary Achievement - Adilla, Alisya; Nurweni, Ari; Nisa, Khairun (English Language Education Study Program, 2024)
Abstract. This study investigates the effect of semantic mapping on improving vocabulary achievement among tenth-grade English as a Foreign Language (EFL) students at MAN 2 Bandar Lampung. A total of 30 students from class X-C participated in the study. Two treatment sessions were conducted in which student’s categorized content words (nouns, verbs, adjectives, and adverbs) in procedure texts using semantic maps. The results of a paired-sample t-test revealed a significant overall improvement in vocabulary achievement, with the mean score increasing from 42.84 in the pre-test to 63.34 in the post-test (p < 0.05). To compare the improvements across the four vocabulary aspects, a Two-Way ANOVA was conducted. The analysis showed significant differences in performance between the pre-test and post-test for each aspect, with nouns showing the highest gain (31%), followed by adverbs (25%), adjectives (22%), and verbs (21%). The interaction effect between the test (pre-test and post-test) and aspect (noun, verb, adjective, and adverb) was also significant, indicating that the improvement varied across the different aspects of vocabulary. These findings support the effectiveness of semantic mapping as a valuable tool for enhancing vocabulary achievement in EFL learners.